Effect of statins on hearing function and subjective tinnitus in hyperlipidemic patients - Yücel Hilal; Yücel Abitter; Arbağ Hamdi; Cure Erkan; Eryilmaz Mehmet Akif; Özer Ahmet Bedri (Sciendo, 2019)
Introduction. It is known that hyperlipidemia reduces hearing functions. In this study, we aimed to study the effect of antihyperlipidemic drugs on hearing functions and tinnitus.